Evaluation of food insecurity and its association with food consumption and some variables among college students - Özge Mengi Celik; Caner Ozyildirim; Merve Seyda Karacil Ermumcu (Journal of Health, Population and Nutrition, 2023)
Abstract Background Students are an important group threatened by food insecurity. Food insecurity among college students is one of the research topics that is attracting attention worldwide, and interest in this topic is growing by the day. Food insecurity has a negative impact on students' biological, mental and social health. This study aimed to determine the prevalence of food insecurity and correlate it with frequency of food consumption and some variables among undergraduate students. Methods This descriptive-analytical study was conducted with 1149 university students at Akdeniz University, Antalya, Turkey. The demographic characteristics of the individuals (gender, age, living situation, income status, and health information), anthropometric measurements (body weight and height), nutritional habits, frequency of food consumption, and Household Food Insecurity Access Scale (HFIAS) were questioned. Statistical Package for the Social Sciences (SPSS) software was used for statistical analyses. Results It was found that 13.1% of the students have mild, 13.0% moderate, and 9.4% severe food insecurity. The rate of individuals with and without food security differs according to gender, living situation, and income status (p < 0.05). There was a statistically significant correlations between the food insecurity score and age (p = 0.047), the number of main meals (p < 0.001) and snacks (0.007), and consumption frequency of certain foods (p < 0.05). Conclusions The prevalance of students facing food insecurity was high. Individuals with food insecurity have a lower frequency of healthy food consumption than individuals with food security. Steps should be taken to ensure nutritional security among undergraduate students, who are the young adult population.